Role of p53 in Regulating Radiation Responses - Ryuji Okazaki (Life, 2022)
p53 is known as the guardian of the genome and plays various roles in DNA damage and cancer suppression. The p53 gene was found to express multiple p53 splice variants (isoforms) in a physiological, tissue-dependent manner. The various genes that up- and down-regulated p53 are involved in cell viability, senescence, inflammation, and carcinogenesis. Moreover, p53 affects the radioadaptive response. Given that several studies have already been published on p53, this review presents its role in the response to gamma irradiation by interacting with MDM2, NF-κB, and miRNA, as well as in the inflammation processes, senescence, carcinogenesis, and radiation adaptive responses. Finally, the potential of p53 as a biomarker is discussed.